A proteomic approach to the development of DIVA ELISA distinguishing pigs infected with Salmonella Typhimurium and pigs vaccinated with a Salmonella Typhimurium-based inactivated vaccine - Gebauer, Jan; Kudlackova, Hana; Kosina, Marcel; Kovarcik, Kamil; Tesarik, Radek; Osvaldova, Alena; Faldyna, Martin; Matiasovic, Jan (BMC veterinary research, 2016)
BACKGROUND: Salmonella enterica serovar Typhimurium is one of the most common enteropathogenic bacteria found in pigs in Europe. In our previous work, we demonstrated the protective effects in suckling piglets when their dams had been vaccinated with an S. Typhimurium-based inactivated vaccine. This study is focused on a procedure leading to serological discrimination between vaccinated and infected pigs. As we supposed, distinct environment during natural infection and in bacterial cultures used for vaccine preparation led to a slightly different spectrum of expressed S. Typhimurium proteins. The examination of porcine antibodies produced after the experimental infection with S. Typhimurium or after vaccination with S. Typhimurium-based inactivated vaccine by affinity chromatography and mass spectrometry revealed differences in antibody response applicable for serological differentiation of infected from vaccinated animals. RESULTS: Antibodies against Salmonella SipB, SipD and SseB proteins were detected at much higher levels in post-infection sera in comparison with control and post-vaccination sera. On the other hand, proteins BamB, OppA and a fragment of FliC interacted with antibodies from post-vaccination sera with a much higher intensity than from control and post-infection sera. In addition, we constructed ELISA assays using post-infection antigen - SipB protein and post-vaccination antigen - FliC-fragment and evaluated them on a panel of individual porcine sera. CONCLUSIONS: The analysis of antibody response of infected and vaccinated pigs by proteomic tools enabled to identify S. Typhimurium antigens useful for distinguishing infected from vaccinated animals. This approach can be utilized in other challenges where DIVA vaccine and a subsequent serological assay are required, especially when genetic modification of a vaccine strain is not desirable.
Keywords: Salmonella Infections, Animal; Proteomics; zvířata; DIVA vaccine; Salmonella Typhimurium; Mass spectrometry; salmonelová infekce u zvířat; prasata; Porcine; Recombinant protein; Animals; salmonelové vakcíny; antigeny bakteriální; Enzyme-Linked Immunosorbent Assay; Swine Diseases; ELISA; proteomika; Antibodies, Bacterial; Antigens, Bacterial; nemoci prasat; protilátky bakteriální; Salmonella Vaccines; Swine; Vaccines, Inactivated; Salmonella typhimurium; inaktivované vakcíny